2015
DOI: 10.3177/jnsv.61.338
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Intake from Beverages in Japan over an 18-Year Period (1996–2013): Trends by Year, Age, Gender and Season

Abstract: Summary An association between the dietary intake of polyphenols and human health has been shown in many epidemiological studies. Since beverages are rich sources of polyphenols, we aimed to evaluate the polyphenol intake from beverages in Japanese individuals with a focus on differences according to year, age, gender and season. More than 10,000 Japanese male and female subjects aged 1-99 y old participated in this survey every year from 1996 to 2013, and their beverage consumption and amount of polyphenol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Our present subjects' polyphenol consumption was largely attributed to coffee and green tea, which is consistent with our previous studies in several Japanese populations [12][13][14][15][16][17]. The main polyphenolic compounds of coffee are hydroxycinnamic acids including chlorogenic acids, whereas green tea contains some flavonoids, mainly catechins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our present subjects' polyphenol consumption was largely attributed to coffee and green tea, which is consistent with our previous studies in several Japanese populations [12][13][14][15][16][17]. The main polyphenolic compounds of coffee are hydroxycinnamic acids including chlorogenic acids, whereas green tea contains some flavonoids, mainly catechins.…”
Section: Discussionsupporting
confidence: 91%
“…Since Japan has a unique food culture, we established an original database for the polyphenol content of foods consumed in Japan to precisely estimate the daily polyphenol intake by Japanese individuals. Using the database, we have estimated the total polyphenol intake in several Japanese populations [12][13][14][15][16][17]. The intake patterns of polyphenol vary among countries; Japanese consume polyphenols largely from beverages (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are major compounds present in many plant foods and beverages, such as coffee, teas, vegetables, and fruits (1). We developed an original polyphenol content database and estimated the total polyphenol intake in several Japanese adult populations (2)(3)(4)(5)(6)(7)(8). Based on the findings obtained in those studies, we documented that beverages were a larger source of total polyphenol (approx.…”
mentioning
confidence: 99%
“…We have developed an original polyphenol content database and estimated the total polyphenol intake in several Japanese populations using non-weighed dietary records (DRs) (only for beverages or menu-based diet) or food frequency questionnaires (FFQs) (12)(13)(14)(15). Our previous studies consistently identified that beverages accounted for approx.…”
mentioning
confidence: 99%
“…Our previous studies consistently identified that beverages accounted for approx. 80% of the total intake, and that coffee and green tea were the major sources of dietary polyphenol in Japanese populations (12)(13)(14)(15).…”
mentioning
confidence: 99%